2017
DOI: 10.3934/jimo.2016019
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order sensitivity analysis in set-valued optimization under Henig efficiency

Abstract: The behavior of the perturbation map is analyzed quantitatively by using the concept of higher-order contingent derivative for the set-valued maps under Henig efficiency. By using the higher-order contingent derivatives and applying a separation theorem for convex sets, some results concerning higher-order sensitivity analysis are established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Optimization of first order discrete and continuous time processes with lumped and distributed parameters has been expanding in all directions at an astonishing rate during the last few decades (see [1,4,5,6,7,8,11,12,13,23,24,25] and their references). The objective of the paper [1] is to briefly summarize some recent results on Differential Inclusions and their optimal control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of first order discrete and continuous time processes with lumped and distributed parameters has been expanding in all directions at an astonishing rate during the last few decades (see [1,4,5,6,7,8,11,12,13,23,24,25] and their references). The objective of the paper [1] is to briefly summarize some recent results on Differential Inclusions and their optimal control.…”
mentioning
confidence: 99%
“…Then, by virtue of the generalized second-order composed contingent epiderivative, are established a unified second-order necessary and sufficient condition of optimality for set-valued optimization problems. In the paper [24] the behavior of the perturbation map is analyzed quantitatively by using the concept of higher-order contingent derivative for the set-valued maps under Henig efficiency. By using the higherorder contingent derivatives and applying a separation theorem for convex sets, some results concerning higher-order sensitivity analysis are established.…”
mentioning
confidence: 99%
“…Optimal control of discretedifferential inclusions with lumped and distributed parameters has been expanding in all directions at an astonishing rate during the last few decades. Note that the differential inclusions are not only models for many dynamical processes but they also provide a powerful tool for various branches of mathematical analysis; see more discussions and comments in the relatively recent publications [9,20,7] and the references therein. First order differential inclusions, set-valued maps play a crucial role in the mathematical theory of optimal processes given in the next papers [2,4,6,12].…”
mentioning
confidence: 99%
“…At the same time it is shown that x[•] is feasible, i.e. x(t 1 ), x (t 1 ) ∈ Q.Then by virtue of (19),(20) and second order functional transversality inclusion (c) at t = t 1 for an arbitrary feasible solution x(•) by analogy with the proof of Theorem 3.1 we deduce that J[x(t)] ≥ J[x(t)], ∀x(•), that is,x(•) is optimal.…”
mentioning
confidence: 99%